Antecedent factors of business planning in the new venture emergence in China. Issue 3 (1st August 2016) - Long, Dan; Geng, Lan; Shakeel, Muhammad
Abstract : Purpose: The purpose of this paper is to build a research model from the perspectives of entrepreneur and entrepreneurial opportunity examining the effects of entrepreneurial growth aspiration and the innovativeness of entrepreneurial opportunity and their interactive effect on the business planning in the new venture emergence. Design/methodology/approach: Six hypotheses are put forward and examined by hierarchical multiple linear regression and multiple logistic regression. The data of this paper are based on the first two rounds of survey data from Chinese Panel Study of Entrepreneurial Dynamics. Findings: The empirical results show that entrepreneurial growth aspiration has significant positive effects on the business planning, namely, compared to the comfortable size entrepreneurs, the growth-oriented entrepreneurs are more likely to do the business planning in the new venture emergence. Different from prior discoveries, the innovativeness of opportunity has no effect on the business planning, but it positively influences the time of doing business planning, and entrepreneurial growth aspiration has a positive moderate effect on this relationship. Research limitations/implications: Entrepreneurial growth aspiration in this paper is divided into growth-oriented entrepreneur and comfortable size entrepreneur from the single perspective of scale. Future research should define growth aspiration as a continuous variable in light of several dimensionalities. Practical implications: The findings are useful for entrepreneurs to make rational and effective decisions whether to do business planning and when to do on the basis of their growth aspiration and the innovativeness of opportunity. The growth-oriented entrepreneur should do the business planning in the new venture emergence. The higher innovative the opportunity is, the latter the entrepreneur had better do the business planning. Besides, it provides the theoretical foundation for entrepreneurship training courses about business planning offered by governments, educational institutions and social training institutions. Originality/value: This paper absorbs growth aspiration into the analysis framework about business planning based on expectancy theory, making up for deficiencies that prior researches excessively focus on entrepreneurial experience and opportunity. Additionally, the study will inspire scholars to research the mechanism of action relative to business planning from the interactive relationship between entrepreneur and entrepreneurial opportunity.